Phytochemical analysis of flower from Pandanus odorifer (Forssk.) Kuntze for industrial application. Issue 20 (18th October 2018) - Nasim, Noohi; Behera, Jay Krishna; Sandeep, I. Sriram; RamaRao, V. V.; Kar, Basudeba; Mishra, Antaryami; Nayak, Sanghamitra; Mohanty, Sujata
Abstract: Pandanus odorifer (Forssk.) Kuntze is an economically important aromatic plant. The essential oil from male flowers is widely used in aromatherapy, cosmetics and as food flavouring agent. Phenylethyl methyl ether (PEME), the major constituent of essential oil, gives the chief characteristic fragrance to the oil. In the present study, 180 samples from 12 different regions were collected and hydrodistilled for essential oil isolation. The oil was then subjected to GC and GC-MS analysis to find out the percentage of the constituents. The results revealed PEME as the major constituent ranging from 58.03 to 81.86% and terpinen-4-ol, the second major constituent ranging from 7.81 to 21.46%. Soil nitrogen was found to be the most influential factor for oil yield and PEME content. The flowers containing high essential oil yield and PEME content could be used as elite chemotypes with enough potential for large-scale commercial cultivation to meet the demand of kewda industries. Abstract :